Study of monolithic integrated solar blind GaN-based photodetectors. (1st February 2018) - Wang, Ling; Zhang, Yan; Li, Xiaojuan; Xie, Jing; Wang, Jiqiang; Li, Xiangyang
Abstract: Monolithic integrated solar blind devices on the GaN-based epilayer, which can directly readout voltage signal, were fabricated and studied. Unlike conventional GaN-based photodiodes, the integrated devices can finish those steps: generation, accumulation of carriers and conversion of carriers to voltage. In the test process, the resetting voltage was square wave with the frequency of 15 and 110 Hz, its maximal voltage of ∼2.5 V. Under LEDs illumination, the maximum of voltage swing is about 2.5 V, and the rise time of voltage swing from 0 to 2.5 V is only about 1.6 ms. However, in dark condition, the node voltage between detector and capacitance nearly decline to zero with time when the resetting voltage was equal to zero. It is found that the leakage current in the circuit gives rise to discharge of the integrated charge. Storage mode operation can offer gain, which is advantage to detection of weak photo signal.